Research note: derivations of gradients in angle‐independent joint migration inversion. (22nd February 2019) - Sun, Yimin; Verschuur, Eric; Qu, Shan
ABSTRACT: Although joint migration inversion has been proposed for several years, a thorough derivation and description of the involved gradients was not published. In this paper, we derive the gradient of both the angle‐independent reflectivity and the velocity in a framework of acoustic angle‐independent joint migration inversion. With some further approximations taken, the conclusions shown in previous publications can also be reached from our new derivation.